Genetic Mapping of Climbing and Mimicry: Two Behavioral Traits Degraded During Silkworm Domestication - Wang, Man; Lin, Yongjian; Zhou, Shiyi; Cui, Yong; Feng, Qili; Yan, Wei; Xiang, Hui (Frontiers in Genetics, 2020)
Behavioral changes caused by domestication in animals is an important issue in evolutionary biology. The silkworm, Bombyx mori, is an ideal fully domesticated insect model for studying both convergent domestication and behavior evolution. We explored the genetic basis of climbing for foraging and mimicry, two degraded behaviors during silkworm domestication, in combination of bulked segregant analysis (BSA) and selection sweep screening. One candidate gene ASNA1, located in the 3~5 Mb on chromosome 19, harboring a specific non-synonymous mutation in domestic silkworm, might be involved in climbing ability. This mutation was under positive selection in Lepidoptera, strongly suggesting its potential function in silkworm domestication. Nine candidate domesticated genes related to mimicry were identified on chromosome 13, 21 and 27. Most of the candidate domesticated genes were generally expressed at higher levels in the brain of the wild silkworm. This study provides valuable information for deciphering the molecular basis of behavioral changes associated with silkworm domestication.